Effect of Paclobutrazol and Brassinosteroid elicitors on expression gene 1-deoxy xylulose-5-phosphate reductoisomerase and its relationship with the biosynthesis of monoterpene carvacrol and thymol in Thymus daenenesis Celak under drought stress - maryam mohamadi farsani; Abdollah Ghasemi Pirbalouti; Gholamreza Bakhshi Khaniki; hasan momtaz (فیزیولوژی محیطی گیاهی, 2016)
Thymus daenensis Celak is a native herb in Iran which belongs to Labiatae family. The herb is widely used in traditional medicine and food industry and has contains secondary metabolites (carvacrol and thymol). Drought stress, affects the growth and metabolism of this plant. In this study, the effects of various levels of drought stress including control (100% field capacity), mild stress (25% field capacity) and severe stress (50% field capacity) with two concentrations (0.5 and 1 µmol /L) Paclobutrazol and also two concentrations (2.5 and 5 µmol /L) of 28-Homobrassinolide dissolved in ethanol were investigated on carvacrol and thymol and oil composition of Thymus daenensis in the pot and outdoorcondition. Also gene expression of 1-deoxy xylulose-5-phosphate reductoisomerase was investigated at various levels of irrigation using quantitative RT-PCR method. The results showed that high gene expression level of 1-deoxy xylulose-5-phosphate reductoisomerase was maximum under complete irrigation and imposing draught stress up to 25% field capacity decreased gene expression significantly. Increasing the draught stress to 50% field also decreased gene expression. The concentrations of carvacrol decreased under severe drought stress upto 25% field capacity in comparison with control and increasing the concentration of 28-Homobrassinolide from 2.5 to 5 µM/L led to a significant increase in the  concentrations of this compound were increased. Moreover, under severe drought stress, the concentration of thymol was increased in the presence of 28-Homobrassinolide solvent (ethanol) in comparison with the control.